Antipsychotic Combinations for Psychiatric Disorders - Noor-Alhooda Milood Al-Awkally; Hamza Khalifa Ibrahim; Abdul Samad (BULLET : Jurnal Multidisiplin Ilmu, 2022)
DEAR EDITOR: Antipsychotic combinations are the co-prescribing of more than one antipsychotic medication for a single psychiatric individual. It's traditionally used to prevent a variety of mental illnesses, such as schizoaffective disorder and cognitive deficits.Overall, the estimated prevalence of antipsychotic combinations ranges between 4% and 70% [1]. Recent evidence indicates that the aforementioned countries have a greater incidence of antipsychotic combinations: [4,5], Arizona, United States (27.1%) [6,] South Africa (28.4%) [7], Ethiopia (28.2%) [8,] China (13.7%) [9], and Japan (19.9%). The observed changes could be likened to the definition of antipsychotic medications, the availability of health coverage for individuals with psychiatric disorders, and healthcare experts' neuropsychology knowledge [10]. Numerous considerations have been linked to an increased prevalence rate of antipsychotic combinations in psychiatric patients. Intervention resistance, switching of medication, aims to justify elevated dose of one antipsychotic, sleeplessness, and the use of antipsychotic medications in the prevention of chronic psychotic comorbid conditions are among these considerations [11]. Other research has discovered that antipsychotic combinations are closely linked with in-patient medical services, the intensity of disease, and doctor choice. [4,5,12]. Extrapyramidal symptoms (EPS) (e.g., peripheral neuropathy, dyskinesia and irritability, dystonia), neuroleptic malignant disorder, elevated prolactin, and loss of libido are all attributed with antipsychotic combinations [13]. Furthermore, antipsychotic overtreatment may significantly raise cardiovascular risk adverse effects, excess weight, carbohydrate disruption, hypercholesterolemia, metabolic syndrome, insulin resistance, postural hypotension, QTC length, sudden cardiac arrest, and death. Sedation, memory deficits, hyper salivation, leukocytosis, immune thrombocytopenia neutropenia, convulsions, and hepatic encephalopathy are also side effects [13]. Antipsychotic overtreatment is a frequently reported treatment for patients suffering from neuropsychiatric disorders [14] . Regrettably, it should be more the exception than the rule, and many patients should avoid it [15,16] . More notably, the scarcity of evidence emphasizes the critical need for future investigations into the benefits and drawbacks of Antipsychotic overtreatment, as well as successful methods within currently prescribed psychotropic medications. Furthermore, antipsychotic combinations can serve to minimize and regulate many psychotic symptoms, such as false beliefs, mental confusion, fear, and extreme irritability. Furthermore, it can help to keep such signs from recurring.